Examining the impact of information processing on CSR communication response. Issue 4 (8th August 2021) - Overton, Holly; Yang, Fan
ABSTRACT: This study tests arguments from the situational theory in the context of CSR communication with information processing as an antecedent. Differential message framing is examined as a moderating variable. A 4 × 1 online experiment was conducted to examine how differential CSR message framing may impact the relationship between different types of information processing and individuals' problem recognition, constraint recognition, and involvement recognition about an environmental issue to drive information seeking behaviors. Structural equation modeling was used to examine significant paths between variables, thus creating a proposed model for understanding how people process information and how this can guide CSR communication strategy. This study aims to fill a theoretical gap in our understanding of CSR communication by examining the effect of information processing on individuals' CSR communication response.